Microstructure and mechanical properties of ODS Fe14Cr model alloy processed by equal channel angular pressing. (November 2014) - Auger, M. A.; Leguey, T.; de Castro, V.; Monge, M. A.; Pareja, R.
<x content-type="archive" xml:space="preserve">Abstract</x> A nanograin sized model oxide dispersion strengthened (ODS) ferritic steel with nominal composition Fe–14Cr–0·3Y2O3 (wt-%) was produced by mechanical alloying and consolidated by hot isostatic pressing. The alloy was submitted to severe plastic deformation by equal channel angular pressing (ECAP). Microstructural and mechanical characterisation was performed before and after ECAP. It was found that ECAP decreases and homogenises grain size without altering the nanoparticle dispersion, in addition to enhancing ductility and shifting the strength drop at high temperatures.